Maxillary right second molar with two palatal root canals - Prashanth, M B (Medknow Publications, 2010)
We report a clinical case of maxillary right second molar with two palatal root canals. The morphology is atypical because it is characterized by two palatal roots with two canals with widely separated orifices and canals. Modifications to the normal access opening and examination of the pulpal floor for additional canals are stressed.